Implementasi Metode Tebak Kata dalam Meningkatkan Keterampilan Berbicara Siswa - Daulay, Irma Sari; Hasibuan, Sutan Botung; Pasaribu, Indah Sri Rahayu (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Speaking skills play an important role in giving birth to a future generation that is intelligent, creative, critical and cultured. Through mastery of speaking skills, students are able to express their thoughts intelligently according to the material and situation when they are speaking. The aim of this research is to find out how the implementation of the word guessing method improves students' speaking skills. The type of research used is classroom action research (PTK) with two cycles. The research subjects were 25 people consisting of 11 men and 14 women. Data collection techniques in this research were obtained through observation and tests. The research results obtained in cycle I were 4 students or 16.00%